Quantitative phenotypic and network analysis of 1q44 microdeletion for microcephaly. Issue 4 (22nd March 2017) - Raun, Nicholas; Mailo, Janette; Spinelli, Egidio; He, Xu; McAvena, Sarah; Brand, Logan; O'Sullivan, Julia; Andersen, John; Richer, Lawrence; Tang‐Wai, Richard; Bolduc, Francois V.
Abstract : As genome wide techniques become more common, an increasing proportion of patients with intellectual disability (ID) are found to have genetic defects allowing genotype–phenotype correlations. Previously, AKT3 deletion was suggested to be responsible for microcephaly in patients with 1q43‐q44 deletion syndrome, but this does not correspond to all cases. We report a case of a de novo 1q44 deletion in an 8‐year‐old boy with microcephaly in whom AKT3 is not deleted. We used a systematic review of the literature, our patient, and network analysis to gain a better understanding of the genetic basis of microcephaly in 1q deletion patients. Our analysis showed that while AKT3 deletion is associated with more severe (≤3 SD) microcephaly in 1q43‐q44 deletion patients, other genes may contribute to microcephaly in AKT3 intact patients with microcephaly and 1q43‐44 deletion syndrome. We identified a potential role for HNRNPU, SMYD3, NLRP3, and KIF26B in microcephaly. Overall, our study highlights the need for network analysis and quantitative measures reporting in the phenotypic analysis of a complex genetic syndrome related to copy number variation.